Unwinding and Rewinding: Double Faces of Helicase? - Wu, Yuliang (Journal of Nucleic Acids, 2012)
Helicases are enzymes that use ATP-driven motor force to unwind double-stranded DNA or RNA. Recently, increasing evidence demonstrates that some helicases also possess rewinding activity—in other words, they can anneal two complementary single-stranded nucleic acids. All five members of the human RecQ helicase family, helicase PIF1, mitochondrial helicase TWINKLE, and helicase/nuclease Dna2 have been shown to possess strand-annealing activity. Moreover, two recently identified helicases—HARP and AH2 have only ATP-dependent rewinding activity. These findings not only enhance our understanding of helicase enzymes but also establish the presence of a new type of protein: annealing helicases. This paper discusses what is known about these helicases, focusing on their biochemical activity to zip and unzip double-stranded DNA and/or RNA, their possible regulation mechanisms, and biological functions.